MYC: a complex problem. Issue 3 (March 2023) - Das, Subhendu K.; Lewis, Brian A.; Levens, David
Abstract : The MYC protooncogene functions as a universal amplifier of transcription through interaction with numerous factors and complexes that regulate almost every cellular process. However, a comprehensive model that explains MYC's actions and the interplay governing the complicated dynamics of components of the transcription and replication machinery is still lacking. Here, we review the potency of MYC as an oncogenic driver and how it regulates the broad spectrum of complexes (effectors and regulators). We propose a 'hand-over model' for differential partitioning and trafficking of unstructured MYC via a loose interaction network between various gene-regulatory complexes and factors. Additionally, the article discusses how unstructured-MYC energetically favors efficient modulation of the energy landscape of the transcription cycle. Highlights: As an oncogenic driver, MYC amplifies global transcription by driving pause release and the early transcription, especially of highly expressed genes. It stimulates replication by facilitating assembly of replication complexes at origins and by associating with replication forks. It facilitates these processes by joining with a wide variety of gene regulatory complexes. Beyond helping to recruit the transcription machinery to promoters, MYC directly up- or down-modulates the catalytic activities of its interaction partners. For example, through assembly with topoisomerases 1 and 2 in the topoisome, MYC dramatically augments the cell's capacity to confront the topological and conformational challenges of DNA and chromatin under high-output mechanical stress. To orchestrate its activities, MYC levels must be strictly tuned by a series of interdependent enzymes that are responsible for its post-translational modifications, stabilization, destabilization, and trafficking. To coordinate the flux of MYC with its associated complexes, its unstructured regions associate with effectors and complexes at transcription start sites (TSSs) at different stages throughout the transcription cycle. To increase overall transcription output, MYC alters the residence times of components of the transcription machinery and as different complexes are sequentially ferried in and out of promoter regions. The conformational plasticity of MYC's effector regions allow it to adapt to a variety of partners without a prior energetic expense of unfolding or remodeling.